Protective effect of filgotinib in rat endotoxin-induced uveitis model - Erdag, Murat; Balbaba, Mehmet; Ilhan, Nevin; Calik, Ilknur; Ulas, Fatih; Eroksuz, Yesari; Yildirim, Hakan (Springer, 2021)
Purpose To investigate the protective effect of filgotinib in endotoxin-induced uveitis model in rats. Materials and method This study used 24 Wistar Albino rats. Group I (control group) included the healthy controls; in Group II (sham group), only 300 mu g/kg intraperitoneal (ip) lipopolysaccharide (LPS) was administered; and in Group III (treatment group), 3 mg/kg/day filgotinib was administered orally for 10 days followed by 300 mu g/kg ip LPS. In all groups, clinical activity scores were evaluated after 24 h. Moreover, histopathological and immunological examinations were performed. Results In Groups I, II, and III, the mean clinical activity and histopathological examination scores were 0.00, 3.25 +/- 0.70, and 1.89 +/- 0.60 and 0.00, 2.88 +/- 1.12, and 1.44 +/- 0.52, respectively. The clinical activity and histopathological examination scores were significantly increased in the sham group compared to the control group (p < 0.05); these findings were significantly reduced in the treatment group (p < 0.05). The mean TNF-alpha and IL-6 ELISA levels in all groups were 50.20 +/- 3.24, 59.87 +/- 2.98, and 54.34 +/- 4.62 and 30.88 +/- 1.79, 36.77 +/- 1.21, and 33.66 +/- 1.86, respectively. The TNF-alpha and IL-6 ELISA levels were significantly decreased in the treatment group compared to the sham group (p < 0.05); there was no significant difference between the treatment group and the control group (p = 0.105, p = 0.067, respectively) Conclusion Filgotinib may be an alternative treatment option in preventing the development of noninfectious uveitis.
Keywords: Filgotinib; Tumor necrosis factor-? Interleukin-6; Uveitis